2021
DOI: 10.3389/fimmu.2021.734188
|View full text |Cite
|
Sign up to set email alerts
|

The Recruitment of Neutrophils to the Tumor Microenvironment Is Regulated by Multiple Mediators

Abstract: Neutrophils sense and migrate towards chemotactic factors released at sites of infection/inflammation and contain the affected area using a variety of effector mechanisms. Aside from these established immune defense functions, neutrophils are emerging as one of the key tumor-infiltrating immune cells that influence cancer progression and metastasis. Neutrophil recruitment to the tumor microenvironment (TME) is mediated by multiple mediators including cytokines, chemokines, lipids, and growth factors that are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 115 publications
(132 reference statements)
1
33
0
Order By: Relevance
“…They did not observe a decreasing neutrophil recrutment at relapse. In our study, we observed that three neutrophil chemotactic factor genes were more frequently lost at relapse but neutrophil recrutment is certainly lead by complementary pathways [24]. Finally, the EORTC study sequenced 287 genes and observed that mutation status changed in approximatively 20% of events with changes observed for all examined genes.…”
Section: Discussionsupporting
confidence: 49%
“…They did not observe a decreasing neutrophil recrutment at relapse. In our study, we observed that three neutrophil chemotactic factor genes were more frequently lost at relapse but neutrophil recrutment is certainly lead by complementary pathways [24]. Finally, the EORTC study sequenced 287 genes and observed that mutation status changed in approximatively 20% of events with changes observed for all examined genes.…”
Section: Discussionsupporting
confidence: 49%
“… Immune cell type Gene markers Spearman’s correlation p -value Ref. General T-cell activation CD3D 0.521 1.34e-26 [ 55 ] CD3E 0.539 8.58e-29 [ 56 ] CD4 + T cells (Th1 and Th2) TBX21 0.509 2.44e-25 [ 57 ] HLA-DMB 0.595 3.77e-36 [ 46 ] HLA-DRA 0.567 2.58e-32 [ 47 ] TGF- β 0.499 3.32e-24 [ 48 ] CRTAM 0.524 5.46e-27 IL12A 0.237 5.083e-6 IL12B 0.381 5.11e-14 Dendritic cells (DCs) VEGFC 0.517 3.36e-25 [ 58 ] CCL4 0.536 2.15e-28 [ 36 ] CCL5 0.536 2.08e-28 CD40L 0.455 6.18e-20 [ 59 ] CD40 0.585 1.15e-34 Neutrophils (N1 population) CXCL5 0.329 1.26e-10 [ 60 ] CSF2 0.391 9.82e-15 [ 61 ] <...…”
Section: Resultsmentioning
confidence: 99%
“…Comparably to inflamed tissues during infection, tumors secrete factors into the circulation that can enhance granulopoiesis and augment infiltration of neutrophils into the TME [31,32]. Here, G-CSF secretion favors hematopoietic cell differentiation toward the neutrophil lineage and enhances the exit of neutrophils into the circulation [33].…”
Section: Secreted Factors That Influence Granulopoiesis and Neutrophi...mentioning
confidence: 99%